2015
DOI: 10.1007/s00248-015-0686-4
|View full text |Cite
|
Sign up to set email alerts
|

Mycobiota of Underground Habitats: Case Study of Harmanecká Cave in Slovakia

Abstract: Harmanecká Cave is located in the Harmanec Valley to the northwest of Banská Bystrica city, in the southern part of the Great Fatra Mountains, Slovakia. This cave is the most important underground locality of bat occurrence in Slovakia (population of 1000 to 1500 individuals). The study aimed at mycological evaluation of the air, the water, and the rock surface of Harmanecká Cave in Slovakia. The samples were taken on 24 July 2014. To examine the air, the Air Ideal 3P sampler was used. Microbiological evaluati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 73 publications
4
21
0
Order By: Relevance
“…Most of the abundant genera observed in our study were also common in other caves, such as Acremonium , Alternaria , Aspergillus , Cephalotrichum , Cladosporium , Fusarium , Penicillium and Trichoderma (Popović et al, ; Vanderwolf et al, ; Zhang et al, ). Talaromyces , which was dominant in rock samples in this study, was also observed by Ogórek, Dylag, Visnovska, Tancinova, and Zalewski () and Ogórek, Višňovská, and Tančinová (). However, we also found uncommon fungi in this study.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Most of the abundant genera observed in our study were also common in other caves, such as Acremonium , Alternaria , Aspergillus , Cephalotrichum , Cladosporium , Fusarium , Penicillium and Trichoderma (Popović et al, ; Vanderwolf et al, ; Zhang et al, ). Talaromyces , which was dominant in rock samples in this study, was also observed by Ogórek, Dylag, Visnovska, Tancinova, and Zalewski () and Ogórek, Višňovská, and Tančinová (). However, we also found uncommon fungi in this study.…”
Section: Discussionsupporting
confidence: 85%
“…Talaromyces, which was dominant in rock samples in this study, was also observed by Ogórek, Dylag, Visnovska, Tancinova, and Zalewski (2016) and Ogórek, Višňovská, and Tančinová (2016). However, we also found uncommon fungi in this study.…”
Section: Community Compositionsupporting
confidence: 77%
See 1 more Smart Citation
“…(Nováková 2009; Bezerra et al 2012; Ogórek et al 2016a, b). The literature also reported that the active growth of this species was found on marten excrement in Domica Cave (Slovakia), but it was identified only by morphological features and without detailed characterization (Nováková 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, microscopic fungi and bacteria may be isolated from various substrates and places in caves and other underground sites such as air, sediments, vermiculations, bat guano, decaying organic material, rock surfaces, bioaerosols, etc. (Nováková 2009; Ogórek et al 2016a, b; Walochnik and Mulec 2009; Vanderwolf et al 2013; Borda et al 2014; Popović et al 2015). …”
Section: Introductionmentioning
confidence: 99%